A Scoping Review on the Role of Access toward achieving Universal Health Coverage in Oral Health. (20th October 2021) - Ghanbarzadegan, A; Balasubramanian, M; Luzzi, L; Brennan, D; Bastani, P
Abstract: Background: Improving access to health services is a way towards achieving Universal Health Coverage (UHC) in oral health. The purpose of this review was to map the determinants of access to dental services within a UHC framework. Methods: Scoping review methods were adopted for the review. PUBMED, Scopus, ISI Web of Science and ProQuest were searched for academic literature on determinants of access to dental services in OCED countries. Articles published in the last 10 years were included. No restriction was placed on study methods; only articles in the English language were included. Qualitative synthesis was conducted, also including trend analysis and mapping exercise Results: A total of 4320 articles were identified in the initial search; 60 articles were included in the qualitative synthesis. The results indicate 7 main themes as the determinants of access to dental services: family level, culture, health status, affordability of services, Social environment, geographic and transportation. Defined determinants of access to dental services, family-level factors, culture and geographical access to dental services, can fill the population axis of the UHC cube. Social environment determinants and affordability of services fill the gap of financial protection as another axis of the UHC cube and finally, availability of dental services and the individual's health status are aligned with the appropriateness of services, the third axis of the UHC cube. Conclusions: This scoping review has identified family-level and cultural, health status, affordability, and availability of services, social environment, and geographic factors contributing towards the inequality in access towards dental services. In addition to considering these main determinants, it is important for policymakers to pay more attention to social and cultural access determinants. Key messages: An exact definition of access to services should be defined and implemented in the dental literature. Health Policymakers besides considering the derived themes of access into dental services should pay attention to social and cultural access determinants.